Genotoxicity evaluation of a hyperosmotic solution proposed as endodontic irrigan = Evaluación de la genotoxicidad de una solución hiperosmótica propuesta como irrigante endodóntico - Muñoz Ruiz, Abraham Israel
One of the main aims of a root-canal treatment is to disinfect the root-canal system through mechanical instrumentation and cleaning by endodontic disinfection solutions. The most common endodontic disinfection solution used has been the sodium hypochlorite. However, it has been reported some important biological adverse effects and risks related to it, so it is necessary to propose and evaluate alternatives to be used as an endodontic disinfection solution. Hyperosmotic solution based on sodium chloride and potassium sorbate previously has been shown an adequate antimicrobial effect against endodontic microorganisms in planktonic and biofilm forms. This study evaluated the genotoxicity of a hyperosmotic solution proposed as an endodontic disinfection solution. Human fibroblast cells were seeded and incubated into well-culture plates and exposed to the hyperosmotic solution (30% and 100%) and compared to NaClO 1%, after cells were cultured, an evaluation was performed by Micronucleus, Tunel and Mitotracker assays. Based on results, the hyperosmotic solution is a safe potential endodontic disinfection solution or adjuvant for root canal system disinfection.